SYSTEM ACCEPTANCE OF DATA IN THE OFFICE OF THE REGENT TANGGERANG LANGUAGE PROGRAMMING USING MICROSOFT VISUAL BASIC 6.0 - Meta Niatama Rangkuti; Sahni Damerianta, SKom, MM (Jurnal Sistem Informasi, 2003)
A fact that human development constantly increasing rapidly. It is up to the inappropriate and harmful for human survival. Hence the need for equitable distribution of population so that each region is occupied by humans is not crowded or so evenly balanced between regions or the one with the other regions. Use of the average resident is to determine the total population of each region and part for know how many people are born, move, migrants and people who have died. Data reception system designed to provide an alternative in population. Use computer records will improve services more quickly. Other than that this system created by Microsoft Visual Basic Programming Language 6.0 is intended to appear easy use by each circle.